2014
DOI: 10.1088/0029-5515/54/2/022004
|View full text |Cite
|
Sign up to set email alerts
|

Stable anisotropic plasma confinement in magnetic configurations with convex–concave field lines

Abstract: It is shown that a combination of the convex and the concave part of a field line provides a strong stabilizing action against convective (flute-interchange) plasma instability (Tsventoukh 2011 Nucl. Fusion 51 112002). This results in internal peaking of the stable plasma pressure profile that is calculated from the collisionless kinetic stability criterion for any magnetic confinement system with combination of mirrors and cusps. Connection of the convex and concave field line parts results in a reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The simple ideal MHD description gives a strong variation in the stable pressure profile due to the strong variation in the specific volume ∫dl/B: the critical profile being p MHD ∝ (∫ dl/B) −5/3 . However, we have found that there is a strong variation in the stable pressure profile at regions of almost equal specific volume-near min ∫ dl/B, with curvature of alternating sign-with appropriate combination of the convex and concave field line parts [15].…”
Section: The Essence Of the Stabilization Effectmentioning
confidence: 77%
See 4 more Smart Citations
“…The simple ideal MHD description gives a strong variation in the stable pressure profile due to the strong variation in the specific volume ∫dl/B: the critical profile being p MHD ∝ (∫ dl/B) −5/3 . However, we have found that there is a strong variation in the stable pressure profile at regions of almost equal specific volume-near min ∫ dl/B, with curvature of alternating sign-with appropriate combination of the convex and concave field line parts [15].…”
Section: The Essence Of the Stabilization Effectmentioning
confidence: 77%
“…It is worth noting that the positions of the min ∫dl, and min λ max = max B min , correspond to the min J and hence to the peaking position for the particles with longitudinal and transverse velocity accordingly [15].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations